2021
DOI: 10.3389/fgene.2021.737906
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection and Genome-wide Association Study for Feed-Efficiency Traits in a Farmed Nile Tilapia (Oreochromis niloticus) Population

Abstract: Nile tilapia is a key aquaculture species with one of the highest production volumes globally. Genetic improvement of feed efficiency via selective breeding is an important goal, and genomic selection may expedite this process. The aims of this study were to 1) dissect the genetic architecture of feed-efficiency traits in a Nile tilapia breeding population, 2) map the genomic regions associated with these traits and identify candidate genes, 3) evaluate the accuracy of breeding value prediction using genomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…Whilst Al-Tobasei et al (2021) found a similar trend when using between 500–1000 SNPs for fillet yield traits. To date, the utilization of low-density panels to decrease the cost of genomic evaluations has also been tested in several aquaculture species, including Atlantic salmon ( Salmo salar ) ( Tsai et al, 2016 ; Correa et al, 2017 ), rainbow trout ( Yoshida et al, 2018 ; Al-Tobasei et al, 2021 ), and Nile tilapia ( Oreochromis niloticus ) ( Yoshida et al, 2019 ; Barría et al, 2021 ), suggesting that the development of cost-effective strategies for applying GS will be key for shaping modern aquaculture breeding programs.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst Al-Tobasei et al (2021) found a similar trend when using between 500–1000 SNPs for fillet yield traits. To date, the utilization of low-density panels to decrease the cost of genomic evaluations has also been tested in several aquaculture species, including Atlantic salmon ( Salmo salar ) ( Tsai et al, 2016 ; Correa et al, 2017 ), rainbow trout ( Yoshida et al, 2018 ; Al-Tobasei et al, 2021 ), and Nile tilapia ( Oreochromis niloticus ) ( Yoshida et al, 2019 ; Barría et al, 2021 ), suggesting that the development of cost-effective strategies for applying GS will be key for shaping modern aquaculture breeding programs.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst Al-Tobasei et al (2021) found a similar trend when using between 500-1000 SNPs for fillet yield traits. To date, the utilization of low-density panels to decrease the cost of genomic evaluations has also been tested in several aquaculture species, including Atlantic salmon ( Salmo salar ) (Correa et al 2017; Tsai et al 2016), rainbow trout (Yoshida et al 2018; Al-Tobasei et al 2021), and Nile tilapia ( Oreochromis niloticus ) (Barría et al 2021; Yoshida et al 2019), suggesting that the development of cost-effective strategies for applying GS will be key for shaping modern aquaculture breeding programs.…”
Section: Resultsmentioning
confidence: 99%
“…To further develop the GIFT strain and to enable future improvements, several studies have been investigating the genetic bases underlying traits of economic interest. As a consequence, Quantitative Trait Loci (QTL) associated with sex determination [11], Tilapia Lake Virus resistance [12, 13], feed efficiency [14], adaptation to oxygen stress [15] in the GIFT strain have now been identified.…”
Section: Introductionmentioning
confidence: 99%